sigma, a repetitive element found adjacent to tRNA genes of yeast. - del Rey, F J (1982)
sigma is a DNA element of about 340 base pairs (bp) that is repeated many times in the yeast genome. The element has 8-bp inverted repeats at its ends and is flanked by 5-bp direct repeats. The 5-bp repeats are different for each sigma and have no homology with the ends of the sigma sequence. sigma is located 16 or 18 bp from the 5' end of several tRNA genes. Southern analysis of different yeast strains shows that the pattern of hybridization is different even for closely related strains.